Translation and Adaptation of the Vocal Fatigue Index into Spanish - Lady Catherine Cantor-Cutiva; María Celina Malebrán Bezerra de Mello; Eric J Hunter (Revista de Investigación e Innovación en Ciencias de la Salud, 2020)
Aim: the purpose of this study was to translate and adapt the English version of the Vocal Fatigue Index (VFI) into the Spanish language.